2008
DOI: 10.3146/ps07-101.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Kernel Moisture Content and Water Activity in Different Maturity Stages of Peanut

Abstract: The water activity (a w ) and kernel moisture content (KMC) of individual Florunner cv. peanut kernels representing five different maturity stages were measured during a period of lateseason drought stress leading up to normal harvest time. Curves were generated describing the relationship between a w and KMC for yellow 1, yellow 2, orange, brown, and black maturity stages as determined by the peanut hull scrape method. As peanuts matured, the KMC for a given a w decreased. KMC in the most immature yellow 1 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
4
0
4
Order By: Relevance
“…Por se tratar de planta com hábito de crescimento indeterminado, mesmo quando a colheita ocorre em momento ótimo, o amendoim apresenta vagens em diferentes estádios de maturação (CARLEY et al, 2008;DORNER, 2008) e também variabilidades em seu teor de água no momento do arranquio e do recolhimento.…”
Section: Introductionunclassified
“…Por se tratar de planta com hábito de crescimento indeterminado, mesmo quando a colheita ocorre em momento ótimo, o amendoim apresenta vagens em diferentes estádios de maturação (CARLEY et al, 2008;DORNER, 2008) e também variabilidades em seu teor de água no momento do arranquio e do recolhimento.…”
Section: Introductionunclassified
“…Por se tratar de planta com hábito de crescimento indeterminado, mesmo quando a colheita ocorre em momento ótimo, o amendoim apresenta vagens em diferentes estádios de maturação (CARLEY et al, 2008;DORNER, 2008). Quando ocorre a colheita prematura, o grande número de vagens imaturas pode acarretar prejuízos econômicos para os produtores e indústria.…”
Section: Introductionunclassified
“…On the other hand, the lower irrigation levels did not have any significant effects on total yield per plot or pod size distribution. As previously suggested for peanut (Heuer et al, 1994;Dorner, 2008), the water situation not only influences the mother plants, but also directly affects the development of the seeds. The effect of irrigation level on pod-filling and other pod-related traits was most significant at the lowest irrigation level (60%), while there was no difference between 80% and 100% irrigation for many other traits (i.e., MC, DE, GPW, PW, SW, L*, a*, b*).…”
Section: Discussionmentioning
confidence: 69%
“…In response to reductions in moisture availability, peanut pod size decreases and its osmotic concentration increases (Boote, Varnell, & Duncan, 1976). Some other studies have also shown that the water activity of the pod wall (pericarp) controls the water balance of the kernels at later developmental stages, which are critical to pod-filling under short-term water-deficit conditions (Heuer et al, 1994;Dorner, 2008). Therefore, pod-filling in peanut is particularly sensitive to irrigation levels during the late-developmental and maturation stages.…”
Section: Introductionmentioning
confidence: 99%